Manajemen Komunikasi dalam Pengembangan Minat Bakat Santri - Faladhin, Johan; Husna, Arina Himatul; Mairita, Desy; Novchi, Raja Widya; Tazri, M.; Marsya, Ulmi (Lembaga penelitian dan pengabdian kepada masyrakat, 2024)
Islamic boarding school are educational institutions with unique character in Indonesia. The increase in the number of Islamic boarding school in various regions from year to year indicates that the education system has gained the trust of many parties. Nowadays, Islamic boarding schools are not only place to deepen religious knowledge but also to develop the potential abilities of their students. The reason is, academic and non-academic achievements need to go hand in hand. Through the observations of the author and team, the Al-Fahmu Kampar Islamic Boarding School has the potential to develop the interests and talents of its students. The formation of interest and talent groups among Islamic boarding school students received a positive response and support, especially from Islamic boarding school leaders. Through opinion polls and interviews with students, the team offered four extracurricular groups based on the arts, namely martial arts, calligraphy, Al-Qur'an recitation and hadrah arts. All discussion and coordination process in this program has been adapted to Islamic boarding school values.